2021
DOI: 10.3389/fpubh.2021.673778
|View full text |Cite
|
Sign up to set email alerts
|

Does Economic Policy Uncertainty Matter for Healthcare Expenditure in China? A Spatial Econometric Analysis

Abstract: A growing body of research has documented the determinants of healthcare expenditure, but no known empirical research has focused on investigating the spatial effects between economic policy uncertainty (EPU) and healthcare expenditure. This study aims to explore the spatial effects of EPU on healthcare expenditure using the panel data of 29 regions in China from 2007 to 2017. Our findings show that healthcare expenditure in China has the characteristics of spatial clustering and spatial spillover effects. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…However, the level of economic development affects the regional medical level and then has an impact on the spread of infectious diseases. Bai et al ( 23 ) uses the panel data of 29 regions in China to explore the impact of EPU on medical expenditure and finds that EPU has a positive spatial spillover effect on medical expenditure. Su et al ( 24 ) found that there was an inverted U-shaped correlation between economic growth and health, and the health promotion effect of economic growth decreased significantly when it exceeded the threshold.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the level of economic development affects the regional medical level and then has an impact on the spread of infectious diseases. Bai et al ( 23 ) uses the panel data of 29 regions in China to explore the impact of EPU on medical expenditure and finds that EPU has a positive spatial spillover effect on medical expenditure. Su et al ( 24 ) found that there was an inverted U-shaped correlation between economic growth and health, and the health promotion effect of economic growth decreased significantly when it exceeded the threshold.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The above conclusions have several important policy implications for China to promote the realization of the goal of "fair medical insurance" and the common prosperity of the elderly during the Fourth 5-Year Plan period (44). As a crucial medical security system design in China, basic medical insurance has a series of tasks such as adjusting the income distribution gap, guaranteeing health rights, and maintaining health justice (45).…”
Section: Discussionmentioning
confidence: 94%
“…The excessive burden of healthcare expenditures has a negative impact on human wellbeing, especially in developing countries. As the world's largest developing country, China faces various challenges, such as insufficient healthcare resources, uneven distribution of healthcare resources, severe air pollution, and an increasingly aging society, all of which contribute to the escalation of healthcare expenditure ( 3 ). In 2021, the average healthcare expenditure per capita was 5,348 RMB, which accounted for 8.8% of total personal expenditures.…”
Section: Introductionmentioning
confidence: 99%